Trimethylolpropane trioleate as eco-friendly lubricant additive - Lee, Chiew Tin; Lee, Mei Bao; Siti Hartini, Hamdan; William Chong, Woei Fong; Chong, Cheng Tung; Hedong, Zhang; Allan Chen, Woei Loon (Elsevier B.V., 2022)
Approximately 17.9% of fuel energy is used to overcome engine friction in passenger cars with engine frictional losses further broken down into losses along hydrodynamic (40%), elastohydrodynamic – due to pure sliding motion (40%), mixed (10%) and boundary (10%) lubrication regimes. Therefore, to assess the tribological influence of TMP trioleate as an eco-friendly additive to a low viscosity Polyalphaolefin (PAO) at different lubrication regimes, the present study adopted a Stribeck-type analysis. Through this study, the viscosity index of PAO was found to increase significantly when blended with 5-vol% TMP trioleate. Tribologically, across the tested conditions at different sliding velocities and applied normal loads, it was determined that this blend could potentially reduce friction power and wear scar diameter by up to 6.09% and 39.65%, respectively, when compared with the neat PAO. Such an improvement was demonstrated to also synergistically enhance the friction modifier effect of this blend at the mixed lubrication regime, delaying the onset of boundary lubrication regime when the contact is lubricated by this mixture.